2020
DOI: 10.5194/cp-16-699-2020
|View full text |Cite
|
Sign up to set email alerts
|

A new multivariable benchmark for Last Glacial Maximum climate simulations

Abstract: Abstract. We present a new global reconstruction of seasonal climates at the Last Glacial Maximum (LGM, 21 000 years BP) made using 3-D variational data assimilation with pollen-based site reconstructions of six climate variables and the ensemble average of the PMIP3—CMIP5 simulations as a prior (initial estimate of LGM climate). We assume that the correlation matrix of the uncertainties in the prior is both spatially and temporally Gaussian, in order to produce a climate reconstruction that is smoothed both f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 61 publications
9
33
0
Order By: Relevance
“…Still, a few locations show considerable differences between the pollen-based and model-based climate anomalies, in line with similar findings mentioned in earlier studies (e.g. ; Beghin et al, 2016;Ludwig et al, 2016;Cleator et al, 2020). These differences could be associated with shortcomings within the RCM and/or uncertainties in the proxy reconstructions (Bartlein et al, 2011;Ludwig et al, 2019;Cleator et al, 2020).…”
Section: Comparison Of the Simulated Land Surface Conditions To Proxy Reconstructionssupporting
confidence: 88%
See 2 more Smart Citations
“…Still, a few locations show considerable differences between the pollen-based and model-based climate anomalies, in line with similar findings mentioned in earlier studies (e.g. ; Beghin et al, 2016;Ludwig et al, 2016;Cleator et al, 2020). These differences could be associated with shortcomings within the RCM and/or uncertainties in the proxy reconstructions (Bartlein et al, 2011;Ludwig et al, 2019;Cleator et al, 2020).…”
Section: Comparison Of the Simulated Land Surface Conditions To Proxy Reconstructionssupporting
confidence: 88%
“…; Beghin et al, 2016;Ludwig et al, 2016;Cleator et al, 2020). These differences could be associated with shortcomings within the RCM and/or uncertainties in the proxy reconstructions (Bartlein et al, 2011;Ludwig et al, 2019;Cleator et al, 2020). Kageyama et al (2006) suggested that terrestrial paleoclimate proxies may be more sensitive to climatic extremes than to the climatological mean state, which could lead to part of the discrepancies between pollen-based reconstructions and the model simulations.…”
Section: Comparison Of the Simulated Land Surface Conditions To Proxy Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the discussion about the lack of modern analogues has focused on interpretation of assemblages of species that are not found together today (Overpeck et al, 1985;Jackson and Williams, 2004;Williams and Shuman, 2008). However, one important non-analogue situation that is ignored in all previous statistical reconstructions is the impact of [CO 2 ] different from today on plant assemblages, with important effects on apparent climatic moisture inferred from pollen data (Prentice et al, 2017;Cleator et al, 2019). Taking the impact of [CO 2 ] into account in our reconstructions reduces the variability of MI during glacial intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that a realistic representation of surface conditions is essential for the accuracy of the simulated regional climate as they play a crucial role in regulating water and energy fluxes between the land surface and the atmosphere (e.g. Crowley and Baum, 1997;Kjellström et al, 2010;Strandberg et al, 2011Strandberg et al, , 2014Gómez-Navarro et al, 2015;Jia et al, 2019a;Ludwig et al, 2017).…”
Section: Introductionmentioning
confidence: 99%